2005
DOI: 10.1158/0008-5472.can-05-0453
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxyglucose as an Energy Restriction Mimetic Agent: Effects on Mammary Carcinogenesis and on Mammary Tumor Cell Growth In vitro

Abstract: Dietary energy restriction (DER) is a potent inhibitor of carcinogenesis, but chronic DER in human populations is difficult to sustain. Consequently, interest exists in identifying energy restriction mimetic agents (ERMAs), agents that provide the health benefits of DER without reducing caloric intake. The selection of a candidate ERMAs for this study was based on evidence that DER inhibits carcinogenesis by limiting glucose availability. The study objective was to determine if 2-deoxyglucose (2-DG), a glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 27 publications
4
92
1
2
Order By: Relevance
“…Because cancer cells are more dependent on glycolysis (Warburg effect), 25 there have been various attempts to block glycolysis as a strategy for inhibiting cancer cells. 8,26 A number of drugs that target mitochondrial oxidative phosphorylation in the tricarboxylic acid cycle, such as AICAR (5-aminoimidazole-4-carboxamide ribonucleotide), oxaloacetate, oligomycin, and metformin, have also been extensively tested. 27,28 In our study, rather than using specific GBM cell lines, we chose GBM-TS, as we believe new therapeutic approaches should target the subpopulation of GBM cells responsible for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Because cancer cells are more dependent on glycolysis (Warburg effect), 25 there have been various attempts to block glycolysis as a strategy for inhibiting cancer cells. 8,26 A number of drugs that target mitochondrial oxidative phosphorylation in the tricarboxylic acid cycle, such as AICAR (5-aminoimidazole-4-carboxamide ribonucleotide), oxaloacetate, oligomycin, and metformin, have also been extensively tested. 27,28 In our study, rather than using specific GBM cell lines, we chose GBM-TS, as we believe new therapeutic approaches should target the subpopulation of GBM cells responsible for treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a number of studies have demonstrated that 2DG treatment in rodents produces a number of effects that parallel those of CR, such as reductions in body temperature, heart rate, and circulating glucose and insulin (5,(15)(16)(17) and increases in circulating glucocorticoids and heat-shock proteins (16)(17)(18). Beyond these effects, 2DG has also been shown to confer functional benefits associated with CR, including inhibition of tumor growth (19,20) and increased stress resistance to neurotoxins and cold shock (17,(21)(22)(23).…”
Section: Glucose and Insulin Homeostasismentioning
confidence: 99%
“…2-Deoxyglucose is a synthetic glucose analogue that inhibits phospho-hexose isomerase in the initial stage of glycolysis (29,33) and induces glucoseregulated stress affecting tumor cells in particular (9,42). The inhibitory effect of 2-DG on tumor growth has been reported in both in vitro (43) and in vivo (5,10) studies. Glycolysis inhibition and resulting energy depletion trigger apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%